Yardstick competition in German municipalities - Jan Finken (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2009)
Does increasing transparency improve fiscal policy behavior of local governments? One way this could take place is via Yardstick Competition between incumbents of neighboring municipalities. This paper contributes to the literature by introducing a simple model which employs probabilistic voting to show the effect of Yardstick Competition on the amount of political rents diverted from the tax revenue. Since additional rents lower the probability of being reelected, the incumbent will reduce equilibrium rents if voters use information on fiscal performance in similar municipalities to evaluate the incumbent's quality. I test this hypothesis on a panel dataset of municipal budget and electoral data in the german state of Northrine-Westphalia. I show evidence for Yardstick Competition in the local business and property tax rates. – – Kann zunehmende Transparenz im kommunalen Budgetprozess die fiskalpolitische Disziplin der politischen Entscheidungsträger verbessern? In dieser Arbeit wird ein positiver Modellrahmen entwickelt, anhand dessen die Wirkungsweise von steigen - der Transparenz auf das Entscheidungsverhalten von Kommunalpolitikern durch den Yardstick Competition Effekt dargestellt werden kann. Politiker reduzieren die Veruntreuung finanzieller Mittel, wenn ihr Verhalten von den Wählern relativ zur Leistung von Politikern in benachbarten Kommunen bewertet wird. Unter Anwendung von Methoden der räumlichen Ökonometrie auf kommunale Haushalts- und Wahldaten der Jahre 1989 bis 2004 wird gezeigt, dass die räumliche Korrelation in den Gewerbe- und Grundsteuerhebesätzen in Nordrhein-Westfalen auf die Existenz von Yardstick Competition zurückzuführen ist.
Keywords: H71; H73; R59; 330; transparency; local public finance; political economics; spatial econometrics; Kommunale Finanzpolitik; Yardstick Competition; Public Choice; Gewerbesteuer; Grundsteuer; Räumliche Interaktion; Schätzung; Nordrhein-Westfalen